The Influence of Promotion and Service Quality on Purchasing Decisions: Study At One of The Car Dealers in Bandung - Puput Rahayu Astuti; Anton Tirta Komara (LPPM STMIK Mardira Indonesia, 2024)
The researcher conducted a study to assess the influence of promotion and service quality on purchasing decisions at a car dealership in Bandung. The study's objective was to examine the primary determinant of service quality on purchasing decisions at the dealership in Bandung. The research involved 95 consumers as participants, who were asked to complete questionnaires. The path analysis research demonstrates the validity of the advertising and service quality variables in influencing purchasing decisions at the vehicle dealership in Bandung. The research results underscore prioritizing promotion and service quality to improve purchasing decisions. The research findings suggest that promotion (X1) has a considerable influence on purchase decisions (Y), and Service Quality (X2) also has a significant impact on purchasing decisions (Y).